HAMBATAN SEKOLAH GRATIS 12 TAHUN (Studi Tentang Penyebab Anak Putus Sekolah SMP dan SMA di Kecamatan Gandus Kotamadya Palembang) - , Gita Isyanawulan, Drs. Suharman, M.Si ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This research is talking about âthe obstacles of free education for 12 yearsâ ( It is studied about the reason why there are still children who are not educated at legal Junior high school and Senior high School in Gandus Subdistrict of Palembang) It is focused at the problem of research. Such as examining the major reason why there are still children who are not educated legally and studying the factors of why this is still happening even the free education has been implemented by South Sumatra government. This research uses qualitative method and it is descriptive. The sources of information are education stakeholder, local people at Gandus Subdistrict who know the background of the problem specifically. The methods to collect the data are interview, observation, and taking documentation to acquire accurate information. The result shown that even the free education program which has been implemented since 2009 is running, but in fact there are still uneducated children. The local peopleâs perception about free education is the parents of children are fully free from payment. The lack of understandings is caused by the information crisis. The real fact is the parents still have responsibilities to pay their children needs for school such as paying uniform and books. Beside that, there are many problems grown caused by the implementation of free education. First, there is discrimination in distributing the facilities between education member RSBI (non free education) and the free education. Second, the students are not serious in studying because they donât pay the cost for education. Third, the attention of parents at education is going lower. Moreover, the reason why there are still children who are not getting the legal education at junior high school and senior high school at Gandus Subdistrict are: first, the lack of motivation for children and young marriage as child factors